Setting the New Standard with Mobile Computing in Online Learning - Shih, Yuhsun Edward; Mills, Dennis (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
Mobile learning represents exciting new frontiers in education and pedagogy. With its "wearable" computing feature and multimedia content delivery, mobile learning offers new benefits to instructors and learners. How do mobile technologies impact our teaching and learning in traditional education? What are the possibilities for m-learning in the various disciplines such as history or English studies? To illustrate these possibilities, this paper presents an application that combines the innovative learning model for mobile learning with an established literature class. This ongoing study focuses on student learning outcomes relative to the benefits and challenges of using mobile learning in the traditional classroom and online learning settings.